2017
DOI: 10.1021/acsnano.7b07734
|View full text |Cite
|
Sign up to set email alerts
|

Live Imaging of Label-Free Graphene Oxide Reveals Critical Factors Causing Oxidative-Stress-Mediated Cellular Responses

Abstract: The interest in graphene and its translation into commercial products has been expanding at a high pace. Based on previously described pulmonary safety concerns for carbon nanomaterials, there is a great need to define parameters guiding interactions between graphene-based materials and the pulmonary system. The aim of the present study was to determine the importance of two critical parameters: lateral dimensions of the material and coating with proteins in relation to each other and their pulmonary impact. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 72 publications
12
106
0
3
Order By: Relevance
“…Recent research found that OM is susceptible to reactive oxygen species (ROS), and the Gram‐ bacteria is easier to be killed in an oxidative stress environment . Although various ROS producing agents are available, such as graphene and its derivatives, iron nanoparticles, noble metal, or doping titanium oxides, it remains a challenge to design a broad‐spectrum antibacterial surface fulfilling the various requirements of titanium implants. For instance, the developed surface must be biocompatible.…”
Section: Introductionsupporting
confidence: 88%
“…Recent research found that OM is susceptible to reactive oxygen species (ROS), and the Gram‐ bacteria is easier to be killed in an oxidative stress environment . Although various ROS producing agents are available, such as graphene and its derivatives, iron nanoparticles, noble metal, or doping titanium oxides, it remains a challenge to design a broad‐spectrum antibacterial surface fulfilling the various requirements of titanium implants. For instance, the developed surface must be biocompatible.…”
Section: Introductionsupporting
confidence: 88%
“…These vesicles sequestered the material for more than 24 h in the apical region of the cell, with no apparent trafficking taking place towards endosome-lysosomal or extracellular compartments ( Figure S8, Video S3). The same pattern of uptake was found in other non-phagocytic cell lines when GO flakes of similar lateral dimensions were also dispersed in serum-free cell culture medium for the first 4 h 19 . In other studies, GO has been reported to enter cells mainly via endocytosis, although fewlayer GO flakes of lateral dimensions under 10 µm can potentially pierce the cell membrane directly 38 .…”
Section: Discussionsupporting
confidence: 73%
“…Next, we followed the internalization of GO and siRNA in MEFs. Thanks to the intrinsic fluorescence of the material, GO uptake can be monitored by confocal microscopy without further functionalization or labelling, as demonstrated in a previous study from our laboratory 19 . However, fluorophore quenching impeded the visualization of a fluorescently-labelled siRNA complexed onto GO (data not shown).…”
Section: Go:sirna Complexes Internalize In Primary Mouse Cells Withoumentioning
confidence: 91%
See 1 more Smart Citation
“…Among all material properties that can be ascribed for GBM adverse effects, as previously reviewed in details, lateral dimensions, surface chemistry and reactivity, thickness, agglomeration, and the presence or absence of biomolecule corona seem to be the most essential toxicity determinants for GBM nanoforms ( Figure ).…”
Section: General Considerations For the Biocompatibility Of Graphene‐mentioning
confidence: 97%